Penggunaan Teknik Fotogrametri Dalam Rekonstruksi Pahatan Pada Batu Prasasti - Goenawan A Sambodo; Yoyon K. Suprapto; Eko Mulyanto Yuniarno (Balai Arkeologi Yogyakarta, 2020)
This research discusses and applies photogrammetry techniques to determine the depth of the script carvings on some worn-out stone inscriptions so images of scripts can be more readable. Inscriptions are the backbone of ancient Indonesian historical writings. Unfortunately the significance of many such ancient inscriptions can not yet be used optimally since many inscriptions are found in a state of having poor legibility, and this due both to natural as well as human factors. To this day, photogrammetry techniques have not been widely used by Indonesian researchers in order to help analyze existing cultural heritage objects, especially stone inscriptions. In addition to previous photogrammetric techniques reviews, this article also brings forward my experiment on the photogrammetric techniques, especially those directly related to the stone inscriptions. The reconstruction was not intended to interpret the meaning of the scripts, but rather to give epigraphists a new insight into other ways of clarifying worn-out scripts.